PECULIARITIES OF FINANCIAL ANALYSIS OF CURRENT ASSETS OF THEENTERPRISE - LOPATOVSKA, Oksana; NIKOLCHUK, Yuliya; BONDARUK, Svitlana (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article defines that the main condition for effective management of current assets at any enterprise is a detailed analysis of the status, dynamics, structure and efficiency of use of its current assets. A study of the existing scientific approaches to the interpretation of the concept of “current assets” is carried out. The main purpose of current assets of any enterprise, the purpose and main tasks of their analysis are determined. A list of information support for the analysis of current assets of enterprise is formed. The financial analysis of current assets includes the following areas: analysis of their composition and structure; assessment of the optimality of their volume; analysis of sources of formation and assessment of maneuvering; analysis of the turnover of current assets in general and analysis of their individual types, such as: production stocks, accounts receivable and cash; analysis of the preservation and efficient use of current assets. For the purpose of further analysis, the author proposes a classification and procedure for calculating certain types of current assets according to such criteria as: area of placement, form, sources of formation and level of liquidity. A study of existing scientific approaches to identifying indicators of efficiency of use of current assets of enterprise is carried out. Indicators characterizing the state of current assets of an enterprise (total amount of current assets of an enterprise, coefficient of real value of current assets in the property of an enterprise, amount of own working capital, maneuvering ratio, coefficient of provision of current assets with own working capital) and indicators of efficiency of use of current assets (speed of turnover of current assets, turnover ratio of current assets, load factor, efficiency ratio of current assets) are defined and characterized. The methodology for determining the amount of absolute and relative release (additional attraction) of current assets as a result of acceleration (deceleration) of their turnover is considered.